Acute Effect of a Single Session of Pilates on Blood Pressure and Cardiac Autonomic Control in Middle-Aged Adults With Hypertension. Issue 1 (January 2020) - Rocha, Jeferson; Cunha, Felipe A.; Cordeiro, Ricardo; Monteiro, Walace; Pescatello, Linda S.; Farinatti, Paulo
Abstract : Abstract: Rocha, J, Cunha, FA, Cordeiro, R, Monteiro, W, Pescatello, LS, and Farinatti, P. Acute effect of a single session of Pilates on blood pressure and cardiac autonomic control in middle-aged adults with hypertension. J Strength Cond Res 34(1): 114–123, 2020—We investigated the blood pressure (BP) and heart rate variability (HRV) responses to a single session of Pilates among adults with hypertension. Thirteen participants (7 women), aged 44–66 years, underwent Pilates and nonexercise control sessions separated by 48–72 hours in a randomized counterbalanced order. Blood pressure and HRV indices were simultaneously assessed 10 minutes before and 60 minutes after all sessions in the supine position: root mean square of successive differences (rMSSD), percentage of successive normal sinus RR intervals >50 ms (pNN50), SD of all normal sinus RR intervals over 24 hours (SDNN), and low-frequency (LF) and high-frequency (HF) bands. After an acute session of Pilates, the mean values for area under the curve for systolic BP ( p = 0.004, corresponding to −7.4 ± 8.2 mm Hg) and mean arterial pressure ( p = 0.023, corresponding to −5.3 ± 5.4 mm Hg) were significantly lower compared to the control session. No significant difference was detected for diastolic BP (−4.2 ± 4.7 mm Hg, p = 0.106). Concomitant to BP reduction, significant lowering of parasympathetic HRV indices occurred: RR intervals (−64.1 ± 69.9 ms·min −1, p = 0.043), rMSSD (−8.3 ± 15.4 ms·min −1, p = 0.013), pNN50 (−3.6 ± 13%·min −1, p = 0.028), and total power (−3, 089.4 ± 5, 938 m 2 ·min −1, p = 0.037). No difference was found for sympathetic markers: SDNN (−17.7 ± 34.6 ms·min −1, p = 0.100), LF (−5.2 ± 21, 6 n.u.·min −1, p = 0.417), and LF:HF ratio (−0.3 ± 5.2 ratio·min −1, p = 0.422). In conclusion, a single session of Pilates reduced BP by ∼5–8 mm Hg in adults with hypertension during the first 60 minutes of post-exercise recovery. Acute BP reduction was concomitant to lowered cardiac parasympathetic activity. Our findings are promising for the use of Pilates as an alternative exercise modality to lower BP.